2020
DOI: 10.1016/j.addma.2019.100862
|View full text |Cite
|
Sign up to set email alerts
|

Digital image correlation for microstructural analysis of deformation pattern in additively manufactured 316L thin walls

Abstract: In additive manufacturing, the process parameters have a direct impact on the microstructure of the material and consequently on the mechanical properties of the manufactured parts. The purpose of this paper is to explore this relation by characterizing the local microstructural response via in situ tensile test under a scanning electron microscope (SEM) combined with high resolution digital image correlation (HR-DIC) and electron backscatter diffraction (EBSD) maps. The specimens under scrutiny were extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…Eventually, interlayers become regions with the highest local strain as displayed in Figure 3(c). For a similar loading on printed specimens, [4] equally observed localisation at interlayers and [11] reported that interlayers are a crack initiation area.…”
Section: At ε 11mentioning
confidence: 74%
See 2 more Smart Citations
“…Eventually, interlayers become regions with the highest local strain as displayed in Figure 3(c). For a similar loading on printed specimens, [4] equally observed localisation at interlayers and [11] reported that interlayers are a crack initiation area.…”
Section: At ε 11mentioning
confidence: 74%
“…The SS316L powder used had a particle size between 45 − 90 µm. Further discussions concerning these process parameters are available in [4] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. They consist of a thin plate acting as the substrate on top of which a single-track wall wall with a similar thickness is deposited by Laser Cladding as proposed initially in [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies use DIC at a smaller scale to highlight spatial distribution of strain within grains [31][32][33][34]. A combination of these techniques were used in [35] to investigate strain localization pattern in additively manufactured 316 stainless steel and explain the observed macroscopic anisotropy of the material.…”
Section: Introductionmentioning
confidence: 99%